PENGARUH PEMBELAJARAN AKTIF TIPE GIVING QUESTION AND GETTING ANSWER TERHADAP PEMAHAMAN KONSEP MAHASISWA PADA PEMBELAJARAN MATEMATIKA - Nurlev Avana (LP3M STKIP Muhammadiyah Muara Bungo, 2019)
Student learning outcomes look low. This is one factor that can show that students' mastery of mathematical concepts is still weak. This problem is estimated because learning is still centered on the lecturer, to overcome this problem is by implement learning by applying Giving Question and Getting Answer type active learning. This research aims to determine whether students’ conceptual understanding of learning by applying Giving Question and Getting Answer type active learning is better than understanding students' concepts with conventional learning. This type of research is experimental research with the subject random design. The population in this research were STKIP students. The sampling technique is random, selected sample class. The instrument used in this research is the final test of learning in the form of essays. The data obtained were analyzed using normality test, homogeneity test and t-test. Based on the results of data analysis obtained the average learning outcomes of students who received treatment were 77.14 higher and the percentage of each indicator understanding the concept in the higher class. From the results of the t statistic test, it was obtained tcount = 2.44 and ttable = 1.645, so that tcount > ttable and from MINITAB software obtained p-value = 0.010. It can be seen that p-value is smaller than α = 0.05. It can be concluded that the understanding of the concept of students who use Giving Question and Getting Answer type active learning is better.